The Shadow of Horror: A Semiotic Analysis of Cinematic Transitions in Ivanna (2022) - Abigail, Michelle Devina; Intyaswati, Drina; Dharma, Nindya Soraya (Komunikator, 2024)
This research examines the representation of scenes in the movie Ivanna (2022) using the shadow technique through a qualitative approach and Charles Sanders Peirce's semiotic theory. Ivanna is a horror film that tells the story of the spirit of Ivanna, a Dutch woman who was beheaded by Japanese soldiers during their colonization of Indonesia. The depiction of the sadism of the massacre that befell Ivanna, combined with the time-setting connectivity through the shadow technique, makes the study of how this technique produces a smooth transition between two realities with different time settings a unique and interesting subject. This study, which employs the shadow technique, complements film representation studies, an area that has not been extensively explored. Peirce's semiotics involve categories in the meaning process, commonly referred to as the meaning triangle, which includes the sign, the sign reference, and the sign use. The results show that cinematography effectively presents a visual representation of the narrative, particularly in the horror genre, where light plays a key role in creating tension. In conclusion, Ivanna successfully combines both elements to convey messages and enhance the audience's experience.